Are some feasibility studies more feasible than others? A review of the outcomes of feasibility studies on the ISRCTN registry - Ben Morgan (BMC, 2021)
Abstract Background Feasibility studies are often conducted before committing to a randomised controlled trial (RCT), yet there is little published evidence to inform how useful feasibility studies are, especially in terms of adding or reducing waste in research. This study attempted to examine how many feasibility studies demonstrated that the full trial was feasible and whether some feasibility studies were inherently likely to be feasible or not feasible, based on the topic area and/or research setting. Methods Keyword searches were conducted on the International Standard Randomised Controlled Trials Number (ISRCTN) registry to identify all completed feasibility studies which had been conducted in the UK. Results A total of 625 records from the 1933 identified were reviewed before it became evident that it would be futile to continue. Of 329 feasibility studies identified, 160 had a known outcome (49%), 133 (83%) trials were deemed to be feasible and only 27 (17%) were reported to be non-feasible. There were therefore too few studies to allow the intended comparison of differences in non-feasible studies by topic and/or setting. Conclusions There were too few studies reported as non-feasible to draw any useful conclusions on whether topic and/or setting had an effect. However, the high feasibility rate (83%) may suggest that non-feasible studies are subject to publication bias or that many feasible studies are redundant and may be adding waste to the research pathway.